Nishida tra Hegel e buddhismo - Sull’opportunità di una filosofia interculturale - Fongaro, Enrico (Scenari, 2021)
Starting from an episode about Nishida concerning Heidegger and the Japanese scholar and philosopher Gōichi Miyake, this essay deals with the relationship of Nishida’s philosophy to that of Hegel. Once Nishida’s main theoretical debt with respect to Hegel has been brought to light, the author tries to elucidate the difference between Nishidian and Hegelian philosophy, following some indications of Nishida himself, and finally trying to identify the fundamental irreducibility between the two philosophers focusing in particular on the different role that language plays in their theoretical systems. Finally, returning to Heidegger and the question posed by him of an overcoming of metaphysics, the author proposes to interpret Nishidian thought as an opportunity for intercultural philosophy in our age of globalization.